Integrative taxonomy of the genus Dyscolus (Coleoptera, Carabidae, Platynini) in Ecuadorian Andes - Moret , Pierre; Murienne, Jérôme (European Journal of Taxonomy, 2020)
The genus Dyscolus Dejean, 1831 is a highly speciose taxon of neotropical Carabidae and the major component of high-altitude ground beetle communities in the tropical Andes. The aim of this study is threefold: (i) refine the taxonomic position of the equatorial members of Dyscolus using molecular data, (ii) provide a delimitation of the species found in Ecuador in páramo and montane forest environments based on a robust combination of molecular and morphological data, (iii) describe the new species and take the nomenclatural decisions made necessary by the results of this study. The seclusion of Dyscolus from more basal platynine clades including Platynus, Batenus and Glyptolenus, is supported by a phylogenetic analysis of the COI marker. Twenty-five new species of Dyscolus, most of them microendemic, are described and illustrated: D. aquator Moret sp. nov. (Tandayapa, Pichincha), D. arauzae Moret sp. nov. (Mt Cayambe, Pichincha), D. arborarius Moret sp. nov. (Parque Nacional Yacuri, Loja), D. barragani Moret sp. nov. (Mt Ayapungu, Chimborazo), D. crespoae Moret sp. nov. (Parque Nacional Podocarpus, Zamora-Chinchipe), D. danglesi Moret sp. nov. (Parque Nacional Yacuri, Loja), D. donosoi Moret sp. nov. (Parque Nacional Podocarpus, Zamora-Chinchipe), D. eleonorae Moret sp. nov. (Cotopaxi and Pichincha provinces), D. famelicus Moret sp. nov. (Papallacta, Napo), D. giselae Moret sp. nov. (Reserva Otonga, Cotopaxi), D. globoculus Moret sp. nov. (Parque Nacional Podocarpus, Zamora-Chinchipe), D. gobbii Moret sp. nov. (Guamaní and Mt Antisana, Pichincha), D. incommunis Moret sp. nov. (Tandayapa, Pichincha), D. marini Moret sp. nov. (Parque Nacional Podocarpus, Loja), D. piscator Moret sp. nov. (Guamaní, Napo), D. placitus Moret sp. nov. (Guamaní, Napo), D. ravidus Moret sp. nov. (Parque Nacional Podocarpus, Loja), D. rivinus Moret sp. nov. (Reserva Otonga, Cotopaxi), D. rugitarsis Moret sp. nov. (Parque Nacional Yacuri, Loja), D. ruizi Moret sp. nov. (Parque Nacional Podocarpus, Loja and Zamora), D. salazarae Moret sp. nov. (Parque Nacional Podocarpus, Loja), D. silvestris Moret sp. nov. (Papallacta, Napo), D. sulcipedis Moret sp. nov. (Parque Nacional Yacuri, Loja), D. verecundior Moret sp. nov. (Mt Illiniza and Mt Corazón, Pichincha) and D. verecundissimus Moret sp. nov. (Mt Chimborazo, Chimborazo). Dyscolus palatus Moret, 1998 is newly synonymized with D. denigratus (Bates, 1891). We demonstrate the subgenus Hydrodyscolus Moret, 1996 to be polyphyletic and therefore consider it a junior synonym of Dyscolus Dejean, 1831.